The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.2478/cttr-2013-0425
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Tobaccos: VII: Influence of Atmosphere on the Formation of Gas Phase Constituents

Abstract: Formation profiles have been obtained for methane, ethane, ethene, propane, propene, butanes, butenes, isoprene, formaldehyde, acetaldehyde, acetone, 2-butanone, benzene, and toluene from the thermal decomposition of tobacco in the presence of helium and air. These data show that in helium the temperatures for optimum formation of gas phase constituents were: hydrocarbons, 450°C; aldehydes, 300°C; ketones, 450°C; isoprene, 380° and 475°C; and aromatic hydrocarbons, 450°C. Air enhances the formation of these ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…The total measured amount of acyl radicals represents ∼0.6% of the total aldehyde content in smoke from 2R4F cigarettes . Furthermore, we observed that pyrolysis of tobacco in 5% O 2 in He relative to inert environment at 300 °C increases the concentration of acyl radicals several fold, similar to the increase reported for acetaldehyde . Low molecular weight aldehydes in tobacco smoke are mainly thermal decomposition products of polysaccharides such as cellulose .…”
Section: Resultssupporting
confidence: 80%
“…The total measured amount of acyl radicals represents ∼0.6% of the total aldehyde content in smoke from 2R4F cigarettes . Furthermore, we observed that pyrolysis of tobacco in 5% O 2 in He relative to inert environment at 300 °C increases the concentration of acyl radicals several fold, similar to the increase reported for acetaldehyde . Low molecular weight aldehydes in tobacco smoke are mainly thermal decomposition products of polysaccharides such as cellulose .…”
Section: Resultssupporting
confidence: 80%
“…The water loss around 100°C accounted for approximately 7% of the weight loss. At the end of 200°C, the samples had lost about 17% of their initial weight which was more than the 11% moisture content, suggesting thermal evaporation and possibly onset of some initial thermal decomposition of some tobacco constituents [ 16 , 18 , 19 ]. The heating rates used in Figure 1 are significantly slower than those typically found in a burning cigarette during a puff where the tobacco heating rate can exceed a few hundred degrees per second [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Typically pyrolysis experiments are performed to examine qualitative or quantitative relationships between a proposed precursor and a constituent found in cigarette smoke. 12,13,16 This approach has also been applied in the assessment of ingredients added to cigarettes, 14,17−19 for example, to assess whether or to what extent a specific ingredient will undergo thermal decomposition or be transferred to the smoke intact. Despite their simplicity in comparison to the highly dynamic and complex processes involved in cigarette smoke formation, carefully conducted pyrolysis experiments have been found to be useful in examining aspects of smoke formation mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have found that most of the cigarette smoke “tar” (a collective term used to describe the particulate matter in the smoke aerosol) is produced by incomplete combustion and pyrolysis of tobacco between 300 and 600 °C. Hence, experimental pyrolysis studies on tobacco and tobacco ingredients have long been a significant part of tobacco research to elucidate the smoke formation mechanism. Typically pyrolysis experiments are performed to examine qualitative or quantitative relationships between a proposed precursor and a constituent found in cigarette smoke. ,, This approach has also been applied in the assessment of ingredients added to cigarettes, , for example, to assess whether or to what extent a specific ingredient will undergo thermal decomposition or be transferred to the smoke intact. Despite their simplicity in comparison to the highly dynamic and complex processes involved in cigarette smoke formation, carefully conducted pyrolysis experiments have been found to be useful in examining aspects of smoke formation mechanisms. , …”
Section: Introductionmentioning
confidence: 99%